Pengembangan dan Evaluasi Pemberian Makanan Tambahan Berbasis Ikan Tuna dan Daun Kelor untuk Peningkatan Status Gizi Balita di Desa Tulaan - Rahman, Nasrul; Muliati, Muliati; Suci, Fuji Mutia; Nofinda, Ayu; Mardiana, Fani; Mauliza, Riska; Farda, Sella; Jalil, Ivon (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
This study focuses on the importance of zinc (Zn) as an essential micronutrient in the health of toddlers, especially in children under five years of age. Zinc plays a role in repairing bone tissue and function, and zinc deficiency can lead to stunted growth and potential stunting in toddlers. To address this, this study examines the effects of providing additional food based on Moringa oleifera leaves and seawater fish to toddlers with stunting. The study was conducted on 30 toddlers with stunting and severe stunting nutritional status For 30 days, the toddlers were given additional food based on Moringa leaves and seawater fish. The results of the study showed that after the intervention, blood zinc levels and average height of toddlers increased. There was also a significant relationship between zinc levels and toddler height, indicating that increased zinc levels are closely related to increased height. In conclusion, the provision of additional food based on moringa leaves and sea fish has a positive impact on zinc levels and height of stunted toddlers at the Sedan Health Center, Rembang Regency. This shows that such interventions can have a positive effect on toddler health and have the potential to overcome stunting problems.